Design and characterization of miconazole nitrate loaded nanosponges containing vaginal gels - P.Suresh Kumar; N.Hematheerthani; J.VijayaRatna; V.Saikishore (International Journal of Pharmacy and Analytical Research, 2020)
The objective of the present work is to prepare and evaluate vaginal gels incorporating nanosponges of Miconazole nitrate for systemic delivery of the drug after topical application. Hence efforts were made to prepare miconazole nitrate loaded nanosponges containing vaginal gels using polymers like hydroxy propyl methyl cellulose (HPMC), sodium carboxy methyl cellulose (NaCMC), methyl cellulose (MC) and carbopol. The gel formulations were prepared with a view to improve permeability of drug. The prepared gel were evaluated for P H,Viscosity, Spreadability, Extrudability, Mucoadhesive time and Invitro diffusion study. The gel formulations can be graded in the following order with respect to the rates of diffusion of drug from them: (HPMC) > (Carbopol) .> (NaCMC) > (MC) The correlation coefficient values (r) revealed that the diffusion profiles follows zero order kinetics and the mechanism of drug release was governed by peppas model. The diffusion exponent of release profiles (slope) has a value of (n>0.5), which indicates non fickian diffusion. It was found that the micanazole nitrate loaded nanosponges containing gels prepared with hydroxy propyl methyl cellulose showed good extrudability, homogeneity, spreadability and required diffusion rate in comparison with other formulations and was selected as suitable candidate to be delivered through vaginal route at controlled rate.